Cross-border governance in the European Union - Kramsch, Olivier Thomas, 1963-; Hooper, Barbara, 1945- (London ; New York : Routledge, 2004)
This book discusses and evaluates the problems of governance within the European Union's cross border regions from diversity of perspectives and over a range of selected case studies.
Governing the absent (non- )border -- 'We are only allowed to re-act, not to act': eurocrats' strategies and borderlanders' tactics in a Dutch-German cross-border region / Anke Struver -- De-politicizing labour market indifference and immobility in the European Union / Martin Van Der Velde and Henk Van Houtum -- Governing the mountains: cross-border regionalization in Catalonia / Jouni Hakli -- The EUROREGION from 1991 to 2020: an ephemeral stamp? / Odile Heddebaut -- Cross-border region Espace Mont-Blanc: a territorial 'not-yet'? / Enza Lissandrello -- Governing the march -- Cross-border governance at the future eastern edges of the EU: a regeneration project? / Ann Kennard -- Euregios in changing Europe: Euregio Karelia and Euroregion Pomerania as examples / Petri Virtanen -- The Northern Dimension: 'multiscalar' regionalism in an enlarging European Union / James Wesley Scott -- Post-national governance and transboundary regionalization: spatial partnership formations as democratic exit, loyalty and voice options? / Noralv Veggeland -- Governing the postcolonial limes -- The choreographies of European integration: negotiating trans-frontier cooperation in Iberia / James Derrick Sidaway -- Towards a Mediterranean scale of governance: twenty-first-century urban networks across the 'Inner Sea' / Olivier Kramsch -- Ontologizing the borders of Europe / Barbara Hooper.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: European Union; Regionalism (International organization); Regionalism (International organization) -- Case studies; European Union countries -- Politics and government; Régionalisme (Politique internationale); Régionalisme (Politique internationale) -- Études de cas; LAW -- International; Politics and government; Regionalism (International organization); European Union countries; Openbaar bestuur; Euregio's.; Regionalisme; Case studies